Online teaching and learning in higher education institution in the Northern Philippines - Galanto Ormilla, Rashid Ceazar; Ogano Ongan, May Grace (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study investigates the shift to online education in the Philippines due to the COVID-19 pandemic and its impact on the education system. Understanding this transition is vital as it signifies a significant adaptation affecting both faculty members and students. Conducted at Ifugao State University, Ifugao, Philippines, we employed a convergent parallel design using online surveys and interviews to determine the perceptions of 30 faculty members and 30 students and their experiences regarding pandemic driven online teaching-learning modes. Findings revealed varied satisfaction levels, with students emphasizing time management and comfort with online technologies for successful learning. The study offers insights into the diverse experiences within the online teaching-learning landscape during the pandemic. It highlights the need for faculty training, flexible class schedules, alternative dissemination methods, and institutional support to enhance online teaching-learning strategies.